The PENGARUH MASA TRANSISI COVID-19 TAHUN 2022-2023 TERHADAP JUMLAH PENDONOR DARAH SUKARLA BERDASARKAN JENIS KELAMIN DAN USIA DI SMA NEGERI 1 SEMARANG - Putri Alfishky; Salma Nadiyah; Rina Puspita; Resti Ariani; Hendro Pratomo (LPPM POLBITRADA, 2024)
One of the prosocial activities is voluntary blood donation consisting of Voluntary Blood Donors and Surrogate Blood Donors. In 2021, all activities in the aspect of health services experienced obstacles due to factors from the Covid-19 pandemic, especially blood donation services, so that the number of donors decreased, while the number of blood demand increased. SMA Negeri 1 Semarang is one of the leading schools in Semarang City that routinely holds blood donation activities every year. The purpose of this study is to find out the voluntary blood donors at SMA Negeri 1 Semarang post-Covid-19 in 2022-2023. This research method was descriptive qualitative research using primary and secondary data types. The sampling technique was carried out by non-probability and judgement/purposive sampling which refers to the Krejcie and Morgan formula to determine the sample size. The data is processed using the IBM SPSS application version 25. The results of this study can be concluded that voluntary blood donors based on female gender have increased while male gender has decreased. Blood donors based on the age of 17-19 years have increased while the age of >19 years has decreased.